The prevalence of Active Play in Brazilian children and adolescents: a systematic review - Mendes, Anselmo Alexandre (2018)
A systematic review of the prevalence of Active Play in Brazilian children and adolescents was performed. Only fully available scientific papers that measured Active Play or leisure time physical activity independently from other types of physical activity in Brazilian children and/or adolescents were considered for inclusion. The search for potential articles was performed on the following electronic databases: Pubmed/Medline, Web of Science, Bireme, Scielo and Scopus. Initially, 63 papers met the eligibility criteria. However, after deeply analyzed, seven studies remained and were included in the present review. The overall prevalence of Active Play was 36%, in which varied from 27.2% to 79.3%. Boys presented a prevalence of 47%, ranging from 39,1% to 79.9%, while the prevalence in girls reached 26%, varying from 13.9% to 78.7%. Although the prevalence of Active Play in Brazil in not satisfactory, the potential to present a reliable data regarding this theme should be highlighted. In agreement with some other studies, boys presented a higher prevalence of physical activity than girls. Also, any socioeconomic pattern regarding the prevalence of Active Play in children and adolescents was observed when the results from this study were compared to other studies developed in other countries from several socioeconomic status. The Active Play should be further investigated individually, as a pivotal component of physical activity, as well as its impact on physical inactivity-related comorbidities.